Microfinance Intervention and Health Outcomes of Marginalized People: A Systematic Literature Review (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: People from developing countries may have poor health due to economic constraints. Microfinance institutions provide collateral-free microcredit to the unbanked people for their livelihood improvement. This study aims to assess the impact of microfinance services on the health outcomes of marginalized people.MATERIALS AND METHODS: The research is based on a review of empirical studies, reports, and data. The PubMed search engine was used to locate research publications on microfinance and health. The PubMed Open Database was applied to find the publications using the keywords "microfinance" and "health." All papers that were published from January 1, 2010, to April 15, 2023, were checked for the study. 71 research papers were discovered during the initial inquiry; nine duplicate articles were eliminated, and 13 were irrelevant to the study. Finally, 50 research papers and reports were selected for evaluation.RESULTS: Health outcomes and microfinance intervention are related. Microfinance services are useful to improve access to healthcare, health initiatives/awareness, and funding for healthcare services. When financial services are integrated with health care services, the poor and marginalized people benefit from the microfinance intervention in the diverse areas of health care services such as communicable and non-communicable diseases, food security and nutrition, contraceptives, and mental health risks of intimate partner violence, as well as health awareness, quality of life, social integration, and economic wellbeing.CONCLUSIONS: Financial accessibility is important for promoting the health of the underprivileged. The poor and marginalized individuals gain from the microfinance intervention in the broad spectrum of health care services when financial services are linked with health care services.